Management of Insurance Surplus in Takaful Companies: Factors Influencing Its Formation and Distribution Methods – A Case Study of Salama Saudi Company (Journal of Economic Additions, 2025)
This study analyzes the determinants of insurance surplus and the methods of its distribution,using Salama Insurance Company in Saudi Arabia as a case during 2019–2024. It shows that some factors can be managed by the company, such as underwriting policies that raise contributions and investment policies that increase mudarabah returns. Other factors, however, are beyond its control, including policyholder behavior, sector regulations, and international accounting standards that dictate ratios and rules. The company is obliged to comply with these standards, while its internal policies help enhance surplus creation. The analysis combines theoretical insight with practical application to clarify surplus management.Keywords: insurance surplus, takaful fund, underwriting policies, investment policies, collected contributions.Jel Classification Codes: G22, M41, G32.